The essential genome of Streptococcus agalactiae. (December 2016) - Hooven, Thomas; Catomeris, Andrew; Akabas, Leor; Randis, Tara; Maskell, Duncan; Peters, Sarah; Ott, Sandra; Santana-Cruz, Ivette; Tallon, Luke; Tettelin, Hervé; Ratner, Adam
Abstract Background Next-generation sequencing of transposon-genome junctions from a saturated bacterial mutant library (Tn-seq) is a powerful tool that permits genome-wide determination of the contribution of genes to fitness of the organism under a wide range of experimental conditions. We report development, testing, and results from a Tn-seq system for use inStreptococcus agalactiae (group BStreptococcus ; GBS), an important cause of neonatal sepsis. Methods Our method uses aHimar1 mini-transposon that inserts at genomic TA dinucleotide sites, delivered to GBS on a temperature-sensitive plasmid that is subsequently cured from the bacterial population. In order to establish the GBS essential genome, we performed Tn-seq on DNA collected from three independent mutant libraries—with at least 135, 000 mutants per library—at serial 24 h time points after outgrowth in rich media. Results After statistical analysis of transposon insertion density and distribution, we identified 13.5 % of genes as essential and 1.2 % as critical, with high levels of reproducibility. Essential and critical genes are enriched for fundamental cellular housekeeping functions, such as acyl-tRNA biosynthesis, nucleotide metabolism, and glycolysis. We further validated our system by comparing fitness assignments of homologous genes in GBS and a close bacterial relative, Streptococcus pyogenes, which demonstrated 93 % concordance. Finally, we used our fitness assignments to identify signal transduction pathway components predicted to be essential or critical in GBS. Conclusions We believe that our baseline fitness assignments will be a valuable tool for GBS researchers and that our system has the potential to reveal key pathogenesis gene networks and potential therapeutic/preventative targets.